E-Transportation Effectiveness in Terms of User Satisfaction - Yosi Afandi; Tri Lestariningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
The high mobility of people in Indonesia encourages innovation in the transportation sector. Innovation in the transportation sector, namely online transportation applications, transportation applications aim to simplify and expedite all user activities from the application. Previous research has not discussed the effectiveness of E-transportation based on user satisfaction by testing and assessing the effect of self-efficacy, Perceived Risk and Attitude on E-transportation usage intention using the TAM method. The use of the TAM method to find out about user behavior in accepting new technology (Lestariningsih, Tri, Budi Artono, 2020). The results of the study stated that the perceived usefulness variable was the most dominant variable in influencing the use intention of the go-jek application, which was 0.513 and the least dominant variable was perceived risk, namely with a small original sample estimate of 0.046.